The future of small farms and small food businesses as actors in regional food security: A participatory scenario analysis from Europe and Africa. (October 2022) - Ortiz-Miranda, Dionisio; Moreno-Pérez, Olga; Arnalte-Mur, Laura; Cerrada-Serra, Pedro; Martinez-Gomez, Victor; Adolph, Barbara; Atela, Joanes; Ayambila, Sylvester; Baptista, Isaurinda; Barbu, Raluca; Bjørkhaug, Hilde; Czekaj, Marta; et al.
Highlights: Outcomes of 13 participatory foresight workshops are compared. Small farms' and businesses' contribution to food security is important in three of the four considered scenarios. Concerns on small farms and food businesses relate to the broader rural setting. Weak collective action will hamper the adaptive capacity of small farms.